Clinical impact of c‐MET expression and genetic mutational status in colorectal cancer patients after liver resection. Issue 8 (7th August 2014) - Shoji, Hirokazu; Yamada, Yasuhide; Taniguchi, Hirokazu; Nagashima, Kengo; Okita, Natsuko; Takashima, Atsuo; Honma, Yoshitaka; Iwasa, Satoru; Kato, Ken; Hamaguchi, Tetsuya; Shimada, Yasuhiro
<x xml:space="preserve">Abstract</x> c‐MET is implicated in the pathogenesis and growth of a wide variety of human malignancies, including colorectal cancer (CRC). The aim of the present study was to clarify the association between c‐MET expression and tumor recurrence in CRC patients after curative liver resection, and to evaluate concordance in c‐MET expression and various mutations of KRAS, BRAF and PIK3CA between primary CRC and paired liver metastases. A cohort of patients was tested for c‐MET immunoreactivity (i.e. immunohistochemistry [IHC]) and KRAS, BRAF and PIK3CA mutations. Analyses were performed both on primary tumors and paired liver metastases, and the association between IHC and mutations results were assessed. A total of 108 patients were eligible. A total of 53% of patients underwent simultaneous resection of primary tumors and metastases, and the others underwent metachronous resection. Levels of concordance between primary tumors and metastases were 65.7%, 87.7%, 100% and 95.2% for c‐MET, KRAS, BRAF and PIK3CA, respectively. High levels of c‐MET expression (c‐MET‐high) in the primary tumors were observed in 52% of patients. Relapse‐free survival was significantly shorter for patients with c‐MET‐high primary tumors (9.7 months) than for those with c‐MET‐low primary tumors (21.1 months) (P = 0.013). These results suggest that a high level of genetic concordance in KRAS, BRAF and PIK3CA between primary tumors and liver metastases, and c‐MET‐high in the primary tumors were associated with shorter relapse‐free survival after hepatic metastasectomy.